The Role of the Snakes and Ladders Game in Basic English Skills in Early Childhood - Nurjaman, Iman; Nuraini, Isma; Padlah, Lu’lu Lutfiah; Fortuna, Nabilla Anatasya; Nuary, Guruh (Jurnal Ilmiah Mandala Education (JIME), 2024)
Early childhood education is an important stage in shaping character and basic skills, including English language acquisition. This study aims to explore the effectiveness of the snakes and ladders game in improving basic English skills in early childhood. Using a Classroom Action Research (CAR) method involving two cycles, the snakes and ladders game was modified to include English elements. The results showed that the game not only helped children recognize new vocabulary, but also improved their speaking and listening skills. The social interaction during the game also provided opportunities for children to practice simple conversations in English. Thus, the snakes and ladders game can be a fun and effective learning tool in teaching English in early childhood